Prevalence and penetrance of pathogenic and likely pathogenic LDLR and APOB gene variants linked to familial hypercholesterolemia and increased risk of ischemic heart disease - Dzhumaniiazova, I. K.; Meshkov, A. N.; Daniel, V.V.; Ezhov, M. V.; Zelenova, E. A.; Chubykina, U. V.; Kashtanova, D.A.; Ivanov, M. V.; Matkava, L. R.; Blinova, O. I.; Kumar, N. A.; Fedorov, A. Y.; et al. (Frontiers in Genetics, 2025)
BackgroundFamilial hypercholesterolemia (FH) is a prevalent hereditary disorder, with its monogenic form linked to an elevated risk of early-onset ischemic heart disease. Evaluating the prevalence and penetrance of pathogenic and likely pathogenic variants associated with this disorder would provide valuable information supporting routine FH screening of the general population. Such informed screening would facilitate early identification of at-risk individuals, enabling timely intervention and management.MethodsWe analyzed genetic data from 4,856 individuals with various cardiovascular conditions for pathogenic and likely pathogenic variants in the PCSK9, APOB, and LDLR genes. The evaluation included comprehensive clinical assessments, instrumental examinations, and laboratory tests. All genetic data were obtained through the whole-genome sequencing of blood leukocytes.ResultsA total of 1.77% of participants carried pathogenic or likely pathogenic variants in the LDLR or APOB genes, and none in the PCSK9 gene. After adjusting for sex and age, the risk of ischemic heart disease was 1.3 times higher in carriers of pathogenic or likely pathogenic variants [95% CI 1.18–1.46; p = 5*10-7]. Additionally, the carriers presented with significantly higher levels of total cholesterol and LDL-C (p = 0.00032 and p = 0.0123, respectively).ConclusionFH remains significantly underdiagnosed. Only 10.5% of carriers of pathogenic or likely pathogenic variants in the LDLR and APOB genes had a prior diagnosis of FH. Our findings suggest low diagnostic rates for this disorder in Eastern European populations and highlight the need for routine genetic screening of younger individuals. However, further research is needed to assess the clinical applicability and cost-effectiveness of such screening programs.